Design of citric acid plant - Batang, Kerima P.; Gutierrez, Glenda B.; Ramirez, Fe Irma A. (Quezon City College of Engineering, 1987)
The proposed plant for the manufacture of citric acid is designed to operate at an annual capacity of one million kilograms. This figure is based on the average expected sales of the acid for the next ten years. With the continuing development of industrial firms using this acid, the trend leans towards an increasing demand of the product. At present, there is no company yet engaged in the production of the acid , and so local competition is not a problem to anyone toying with the idea of setting-up a plant. The proposed plant is located at Tuy, Batangas. This site was chosen because of the proximity of the source of raw materials (molasses and bagasse) to the plant, and at the same time, it is not far from other firms needing the product. More so, the place is between the towns of Nasugbu and Balayan where two sugar mills are located from which the raw materials will be coming from. The recommended process proposed is the Cahn method which uses black strap molasses as the main source of sucrose and bagasse as the inert material in the fermentation process. The proposed plant is estimated to cost about Php 69 M. The money to be used would be loaned from the bank, with a 15% interest. The payout time is estimated to be about five years with 9.35% return on investment.
Submitted in partial fulfillment of the requirements in ChE 62.
Keywords: Factories -- Design and construction; Citric acid